THC and CBD affect metabolic syndrome parameters including microbiome in mice fed high fat-cholesterol diet - Jonathan Gorelick; Tal Assa-Glazer; Gil Zandani; Anna Altberg; Noa Sela; Abraham Nyska; Zecharia Madar (BMC, 2022)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is associated with metabolic syndrome, which often includes obesity, diabetes, and dyslipidemia. Several studies in mice and humans have implicated the involvement of the gut microbiome in NAFLD. While cannabis and its phytocannabinoids may potentially be beneficial for treating metabolic disorders such as NAFLD, their effects on liver diseases and gut microbiota profile have yet to be addressed. In this study, we evaluated the therapeutic effects of the two major cannabinoids, delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), on NAFLD progression. Methods NAFLD was induced by feeding mice a high fat-cholesterol diet (HFCD) for 6 weeks. During this period, the individual cannabinoids, THC or CBD, were added to the experimental diets at a concentration of 2.5 or 2.39 mg/kg. Profile of lipids, liver enzymes, glucose tolerance, and gene expression related to carbohydrate lipids metabolism and liver inflammation was analyzed. The effect of THC or CBD on microbiota composition in the gut was evaluated. Results While not alleviating hepatic steatosis, THC or CBD treatment influenced a number of parameters in the HFCD mouse model. CBD increased food intake, improved glucose tolerance, reduced some of the inflammatory response including TNFa and iNOS, and partially mitigated the microbiome dysbiosis observed in the HFCD fed mice. THC produced a much weaker response, only slightly reducing inflammatory-related gene expression and microbiome dysbiosis. Conclusions The results of this study indicate the potential therapeutic effects of individual phytocannabinoids are different from the effects of the cannabis plant possessing a mixture of compounds. While CBD may help ameliorate symptoms of NAFLD, THC alone may not be as effective. This disparity can putatively be explained based on changes in the gut microbiota.